2009
DOI: 10.1111/j.1365-2567.2008.02891.x
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory activity of human umbilical cord blood‐derived mesenchymal stem cells in vitro

Abstract: SummaryBone marrow-derived mesenchymal stem cells (BM-MSC) are currently being investigated in preclinical and clinical settings because of their selfrenewal and multipotent differentiative capacity or their immunosuppressive function. However, BM may be detrimental because of the highly invasive donation procedure and BM-MSC decline with age. Therefore, MSC derived from other sources have been considered as an alternative. However, there is only limited knowledge on their immunomodulatory properties. Human um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
160
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(172 citation statements)
references
References 62 publications
(139 reference statements)
9
160
0
3
Order By: Relevance
“…The morphology, division characteristics, and surface markers of CBMSCs are similar to those of bone marrow-derived MSCs, 59,60 except for some differences in the expression of CD105 and CD44. 61 More important, CBMSCs have also been identified as perivascular cells expressing CD146, platelet-derived growth factor ␤, alkaline phosphatase, and NG2, but not CD34 or CD45.…”
mentioning
confidence: 75%
“…The morphology, division characteristics, and surface markers of CBMSCs are similar to those of bone marrow-derived MSCs, 59,60 except for some differences in the expression of CD105 and CD44. 61 More important, CBMSCs have also been identified as perivascular cells expressing CD146, platelet-derived growth factor ␤, alkaline phosphatase, and NG2, but not CD34 or CD45.…”
mentioning
confidence: 75%
“…hMSCs are traditionally derived from adult tissues, such as adipose and bone marrow, but cells from these sources seem to lose their potential during aging; and, therefore, alternative sources are sought from postnatal tissues, such as umbilical cord blood [1,[5][6][7][8][9]. Umbilical cord blood-derived MSCs (UCBMSC) are now considered a potential substitute for bone marrow-derived mesenchymal stem cell (BMMSC) to overcome the aging problem, as they are derived from an in vivo microenvironment more similar to bone marrow with characteristic properties for hMSCs [5,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppressive treatments that increase graft survival are undesirable, since it has been shown that a correlation exists between the length of exposure to immunosuppressive drugs and the risk of malignancy after stem cell transplantation. Recent results have shown that mesenchymal stem cells from umbilical cord blood, dental pulp, PDL and bone marrow have immunosuppressive properties in vitro [43][44][45]. Moreover, the clonogenic nature of adult stem cells represents an advantage heterogeneous stem cell populations resulting in a more reproducible, potent immunosuppressive effect in patients [46].…”
Section: Safety and Efficacy Issues Of Stem Cell-based Therapies In Denmentioning
confidence: 99%